Diffusion of clindamycin-resistant and erythromycin-resistant methicillin-susceptible Staphylococcus aureus (MSSA), potential ST398, in United States Veterans Health Administration Hospitals, 2003-2014 - Margaret Carrel; Michihiko Goto; Marin L. Schweizer; Michael Z. David; Daniel Livorsi; Eli N. Perencevich (Antimicrobial Resistance and Infection Control, 2017)
Abstract Background Changing phenotypic profiles of methicillin-susceptible Staphylococcus aureus (MSSA) isolates can indicate the emergence of novel sequence types (ST). The diffusion of MSSA ST can be tracked by combining established genotypic profiles with phenotypic surveillance data. ST398 emerged in New York City (NYC) and exhibits resistance to clindamycin and erythromycin but tetracycline susceptibility (“potential ST398”). Trends of potential ST398 were examined in a national cohort of all Veterans Health Administration patients with MSSA invasive infections during 2003–2014. Methods A retrospective cohort of all patients with MSSA invasive infections, defined as a positive clinical culture from a sterile site, during 2003–2014 was created. Only isolates tested against clindamycin, erythromycin and tetracycline were included. Annual hospital-level proportions of potential ST398 were compared according to facility distance from NYC and region. Results A total of 34,025 patient isolates from 136 VA medical centers met the inclusion criteria. Of those, 4582 (13.5%) met the definition of potential ST398. Potential ST398 increased over the 12-year cohort and diffused outwards from NYC. Incidence Rate Ratios of >1.0 (p < 0.01) reflect increases in potential ST398 over time in hospitals nearer to NYC. Conclusions We observe an increase in the phenotypic profile of potential ST398 MSSA isolates in invasive infections in a national cohort of patients in the US. The increase is not evenly distributed across the US but appears to diffuse outwards from NYC. Novel MSSA strain emergence may have important clinical implications, particularly for the use of clindamycin for suspected S. aureus infections.